Case Report: Twin Pregnancy Gives Birth to a Girl with Partial Trisomy 21 Mosaicism after in vitro Fertilization and Embryo Transfer - Guo, Zhenglong; Kang, Bing; Wu, Dong; Xiao, Hai; Hao, Leilei; Hao, Bingtao; Liao, Shixiu (Frontiers in Genetics, 2022)
Objective: To report a rare case in which an IVF-ET twin pregnancy gave birth to a partial trisomy 21 chimera girl. Design: Case report. Setting: University hospital. Patient: A girl with partial trisomy 21 mosaicism after in vitro fertilization and embryo transfer. Interventions:In vitro fertilization (IVF) and embryo transfer (ET). Main Outcome Measure: Karyotype analysis, Copy Number Variation sequencing (CNV-seq), stLFR-WGS, and Short Tandem Repeat (STR) analysis. Results: Being assisted with IVF and EF technology, the couple successfully gave birth to twin sisters at 37 weeks of gestational age. The NonInvasive Prenatal Testing (NIPT) and Nuchal Translucency (NT) examination showed no detectable genetic abnormalities during pregnancy. However, the younger infant displayed growth retardation and feeding difficulties after birth, which was not observed in her twin sister. Further genetic counseling and diagnosis suggested that she is a Chimera with complex partial trisomy 21. The stLFR-WGS assay showed multiple CNV variations in Chr21 and STR analysis confirmed the paternal origin of the additional fragments. Conclusion: It is rare for IVF-ET-assisted twin pregnancy to give birth to a girl with a complex combination of abnormal Chr21, which might result from paternal chromosome rearrangement during meiosis and mitosis.